2019
DOI: 10.1016/j.lwt.2019.02.057
|View full text |Cite
|
Sign up to set email alerts
|

Development of a dairy fouling model to assess the efficacy of cleaning procedures using alkaline and enzymatic products

Abstract: This document is a postprint version of an article published in LWT -Food Scienceand Technology © Elsevier after peer review. To access the final edited and published work see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…In food processing industries, cleaning is based on the removal of residues and harmful microorganisms such as L. monocytogenes to protect food from contamination from surfaces, employing physical or chemical methods [ 103 , 104 ]. Another objective of the cleaning program is to ensure a clean environment for employees, and to prepare equipment and other industrial surfaces in the food area which are difficult to clean, with the aim of extending the product shelf-life and preventing future damage [ 105 , 106 ].…”
Section: Control Strategies Implemented In the Food Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…In food processing industries, cleaning is based on the removal of residues and harmful microorganisms such as L. monocytogenes to protect food from contamination from surfaces, employing physical or chemical methods [ 103 , 104 ]. Another objective of the cleaning program is to ensure a clean environment for employees, and to prepare equipment and other industrial surfaces in the food area which are difficult to clean, with the aim of extending the product shelf-life and preventing future damage [ 105 , 106 ].…”
Section: Control Strategies Implemented In the Food Industrymentioning
confidence: 99%
“…A well implemented cleaning program can help to displace milk deposits, dissolve milk proteins, emulsify fat, and aid the removal of dirt. In Guerrero-Navarro et al [ 103 ], two commercial agents were used, one with chemical components and another which was based on a biological solution, the use of enzymes. The results showed that in the dairy industry, enzymatic cleaning agents obtained better results in terms of eliminating organic matter than chemical agents.…”
Section: Control Strategies Implemented In the Food Industrymentioning
confidence: 99%
“…Recently, cellulases and lipases have been studied alone or in an association against biofilms and removing residual food materials from surfaces. Guerrero-Navarro et al (2019) found that the association of lipase, amylase and protease removed 78% of milk fouling from stainless steel surfaces after enzymatic treatment. Regarding removal of biofilms by lipases, Araújo et al (2017) reported a reduction of 1.34 log CFU/cm 2 of biofilms from P. fluorescens, while complete elimination of M. caseolyticus biofilms was described by Mnif et al (2020).…”
Section: Enzyme-based Approaches For Removal Of Biofilmsmentioning
confidence: 99%
“…Traditionally cleaning consist of a combination of alkaline and acidic cleaning at temperatures ranging from 70 -90°C (Timmerman, Mogensen, & Graßhoff, 2016). As part of the EU project ENTHALPY, a new enzymatic cleaning method was developed (Guerrero-Navarro et al, 2019). Advantage of using enzymes for cleaning are: the lower working temperatures (around 50°C), the reduced amounts of chemical waste, and a reduction in water consumption.…”
Section: Enzymatic Cleaningmentioning
confidence: 99%